Analysis Of Exoneration Clauses In Terms And Use Of The Tik Tok Application - Reni Agustin; Arikha Saputra (LEGAL BRIEF, 2022)
Tik Tok is one of the biggest social media apps with many users. In terms of security and use of their personal data, Tik Tok ensures its users will maintain user data privacy. However, the privacy policy has an exoneration clause stating that Tik Tok cannot guarantee the security of user information transmitted through the platform. Therefore, the user himself bears the risk of any transmission. This provision contradicts Article 18 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection. This shows that Tik Tok is not fully responsible for maintaining the confidentiality of its user data. The exoneration clause is a means for Tik Tok to avoid the obligations that should be its responsibility. The terms and use of the Tik Tok application in protecting the personal data of Tik Tok users are under the Regulation of the Minister of Communication and Information Number 20 of 2016 concerning Protection of Personal Data in Electronic Systems, but not optimally. This is due to the existence of an exoneration clause which frees Tik Tok from its responsibility for the risk of transferring its users’ personal data.